Mineral dating of mantle−derived CO2 charging and its application in the southern Songliao Basin, China. (May 2016) - Qu, Xiyu; Chen, Xiu; Yu, Miao; Liu, Li
Abstract: The timing of mantle−derived CO2 charging in sedimentary basins is the basis for studying CO2 -sandstone interactions and CO2 -oil interactions. In general, the time of the volcanic eruption near the CO2 gas reservoir is considered to be the time of mantle-derived CO2 charging. However, this approach is not suitable for hydrocarbon-bearing basins that have experienced multiple volcanic events. In this paper, using dawsonite-bearing sandstones contained in an oil-bearing CO2 gas and oil reservoir in the southern Songliao Basin as the object of the study on the basis of paragenetic sequence and fluid inclusions, we establish a mineral dating method for determining the time of mantle-derived CO2 charging. In this method, the mineral used for dating is dawsonite, which is formed under a high CO2 partial pressure and records the migration and aggregation of mantle-derived CO2 in geologic history. By interpreting the dawsonite-bearing sandstone in the southern Songliao Basin, we find two hydrocarbon charges and one CO2 charge and that the mantle-derived CO2 charging occurred slightly later than or quasi-simultaneously with the second hydrocarbon filling. Combining the currently known time of hydrocarbon reservoir formation and the time of tectonic fracture development, we deduce that the mantle-derived CO2 formed the dawsonite in the southern Songliao Basin at the end of the Cretaceous (end of the Mingshui period) and the beginning of the Paleogene. Highlights: The dawsonite and mantle−derived CO2 have the same carbon source. Using the dawsonite to determine the time of mantle−derived CO2 charge is realized. The mineral dating fitting for basin with multiple volcanic events is established. Application of the mineral dating in southern Songliao Basin is satisfactory.